Association of Dietary Acid Load with the Prevalence of Metabolic Syndrome among Participants in Baseline Survey of the Japan Multi-Institutional Collaborative Cohort Study - Arisawa, Kokichi; Katsuura-Kamano, Sakurako; Uemura, Hirokazu; Van Tien, Nguyen; Hishida, Asahi; Tamura, Takashi; Kubo, Yoko; Tsukamoto, Mineko; Tanaka, Keitaro; Hara, Megumi; Takezaki, Toshiro; Nishimoto, Daisaku; et al. (Nutrients, 2020)
The association between dietary acid load and metabolic syndrome (MetS) has not been fully investigated. A cross-sectional study was performed on 14,042 men and 14,105 women (aged 35–69 years) who participated in a baseline survey of the Japan Multi-Institutional Collaborative Cohort study. Dietary acid load was assessed using the net-endogenous-acid-production (NEAP) score that is closely correlated with the rate of renal net acid excretion. MetS was diagnosed according to the Joint Interim Statement Criteria of 2009 using body-mass index instead of waist circumference. After adjusting for potential confounders, higher NEAP scores were associated with a significantly increased odds ratio (OR) of MetS, obesity, high blood pressure, and high fasting blood glucose. These associations remained significant after further adjustment for carbohydrate intake or two nutrient-pattern scores significantly associated with MetS. After adjustment for fiber, iron, potassium, and vitamin pattern scores, the OR of MetS for the highest quartile of NEAP scores, relative to the lowest quartile, was 1.25 (95% confidence interval 1.12–1.39). There was no significant interaction between sex, age, or body-mass index and NEAP. Higher dietary acid load was associated with a higher prevalence of MetS and several of its components, independently of carbohydrate intake or nutrient patterns.